Child malnutrition and childhood in Argentina: Current dimensions, trends and views on the problem from the combination of an observational and qualitative design - Longhi, Hugo Fernando (2020)
Introduction: Child malnutrition is the most extreme expression of poverty. Little is known about the characteristics of this problem in the context of an emerging country such as Argentina. This article sought to investigate the magnitudes, trends, scales and other perspectives on childhood malnutrition in the first decades of the 21st century, based on the use of unconventional sources. Material and Methods: Based on statistics of mortality, morbidity and birth weight, indicators of nutritional status in childhood were developed. They were consolidated considering the national and regional scale. A quantitative (observational cross-sectional) and qualitative approach was applied (from interviews with key informants and documentary analysis). Emphasis was placed on the use of sources of a quantitative nature little used for the measurement of this phenomenon, complemented by others of a qualitative nature, carrying out a value criticism that allows us to detect strengths and limitations of both approaches. Results: The results warn –in a general framework of decline– different behaviors according to regions and provinces, identifying sectors of extreme magnitude and worrying trends in this matter. The persistence of the problem in vast sectors of northern Argentina is highlighted, with malnutrition values more similar to the Latin American context than to the rest of the country, as well as the emergence of new associated problems. Conclusions: Nutritional problems in Argentine childhood are currently crossed by remnants of the past –malnutrition among them– and the emergence of new problems, among which overweight and obesity stand out. The results found constitute a relevant input capital to promote concrete actions in child care and protection, differentiated according to the magnitude, trends and spatial location of certain nutritional problems. In effect, the Northern provinces should be a priority for public policies that seek to mitigate or eradicate the current levels of malnutrition in children.